Organizational Culture Management in Forming Student Character Based on Qur'anic Values in Madrasah Ibtidaiyah - Sofia Nisa Ulyantika; Reyhana Nur Azizah; Wijaya Putri; Bambang Sri Anggoro; Sovia Mas Ayu (Assyfa Journal of Islamic Studies, 2026)
This article examines the research aimed to analyze organizational culture management in shaping student character based on Qur'anic values ​​at MI Al Qur'an Trimurjo, Central Lampung. The method used was qualitative research with a case study approach. Data were collected through participatory observation, in-depth interviews with the principal, teachers, and students, and documentation analysis. The results showed that organizational culture management at MI Al Qur'an was implemented through three main stages: planning, implementation, and control. Internalized Qur'anic values ​​include honesty (shiddiq), trustworthiness, discipline, responsibility, and compassion. Featured programs such as the habit of reading the Qur'an, congregational prayer, and memorizing the Qur'an serve as key instruments in shaping student character. Supporting factors include the commitment of all members of the madrasah and parental support, while inhibiting factors include limited time and differences in student backgrounds. This study recommends strengthening ongoing evaluation and active parental involvement in character-building programs based on Qur'anic values.